Columna Traiani - Traianssäule Siegesmonument und Kriegsbericht in Bildern. Beiträge der Tagung in Wien anlässlich des 1900. Jahrestages der Einweihung, 9.-12. Mai 2013 - Mitthof, Fritz; Schörner, Günther (Holzhausen, 2017)
On 12th May 2013 the dedication day of Trajan's Column in Rome was celebrated for the nineteen hundredth time. This anniversary provided the perfect occasion to fully appreciate the outstanding significance of this unique monument by means of an international conference, especially from the perspective of the traditional academic disciplines of Ancient History and Classical Archeology, including many disciplines such as Art History, Religious Studies, Epigraphy, Numismatics, Material Culture Studies and Visual Culture Studies. The volume contains the results of the conference.